Point-of-Care Testing for Anemia, Diabetes, and Hypertension: A Pharmacy-Based Model in Lima, Peru - Enrique M. Saldarriaga; Elisabeth Vodicka; Sayda La Rosa; Maria Valderrama (Ubiquity Press, 2017)
Background: Prevention and control of chronic diseases is a high priority for many low- and middle-income countries. This study evaluated the feasibility and acceptability of training pharmacy workers to provide point-of-care testing for 3 chronic diseases-hypertension, diabetes, and anemia-to improve disease detection and awareness through private pharmacies. Methods: We developed a multiphase training curriculum for pharmacists and pharmacy technicians to build capacity for identification of risk factors, patient education, point-of-care testing, and referral for abnormal results. We conducted a pre-post evaluation with participants and evaluated results using Student 't' test for proportions. We conducted point-of-care testing with pharmacy clients and evaluated acceptability by patient characteristics (age, gender, and type of patient) using multiple logistic regression. Results: In total, 72 pharmacy workers (66%) completed the full training curriculum. Pretest scores indicated that pharmacists had more knowledge and skills in chronic disease risk factors, patient education, and testing than pharmacy technicians. All participants improved their knowledge and skills after the training, and post-test scores indicated that pharmacy technicians achieved the same level of competency as pharmacists ('P' < .01). Additionally, 698 clients received at least 1 test during the study; 53% completed the acceptability survey. Nearly 100% thought the pharmacy could provide faster results, faster and better attention, and better access to basic screening for hypertension, diabetes, and anemia than a traditional health center. Fast service was very important: 41% ranked faster results and 30% ranked faster attention as the most important factor for receiving diagnostic testing in the pharmacy. Discussion: We found that it is both feasible for pharmacies and acceptable to clients to train pharmacy workers to provide point-of-care testing for anemia, diabetes, and hypertension. This innovative approach holds potential to increase early detection of risk factors and bolster disease prevention and management efforts in Peru and other low- and middle-income settings.